Increasing Vocalizations and Echoics in Infants at Risk of Autism Spectrum Disorder - Neimy, Hayley (Behav Anal Pract, 2020)
Infant siblings of children with an autism spectrum disorder (ASD) diagnosis (i.e., infants at risk of ASD) are excellent candidates for early interventions based on the principles of applied behavior analysis. This study replicates and extends behavioral research using contingent social reinforcement procedures (i.e., vocal imitation and motherese speech) to increase both vocalizations and echoics among 3 infants at risk of ASD with their mothers in the natural environment. Results confirmed earlier findings that contingent reinforcement, specifically vocal imitation, reliably produces high rates of vocalizations, echoic approximations, and emerging pure echoic repertoires in at risk infants. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40617-020-00413-2) contains supplementary material, which is available to authorized users.